Sharing and Participation: Mediating Public Library Values through the Social Catalogue - Cavanagh, Mary (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Taking an actor-network approach, this study explores the social catalogue from the perspectives of the designer, library organization and users. Findings indicate that the library and their users have been enrolled into the vendor's blackbox of design structures and templates and that there has been limited use of social media functions. Au moyen de l’approche acteur–réseau, cette étude explore le catalogue social du point de vue du concepteur, de la bibliothèque et de l’usager. Les résultats montrent que la bibliothèque et ses usagers ont accepté les arguments des fournisseurs en matière de design et de gabarits, mais que l’utilisation des fonctions sociales demeure limitée.